Change in the Status of an Individual Company and Its Legal Consequences in Terms of Article 153h of the Government Regulation in Lieu of Law of the Republic of Indonesia Number 2 of 2022 Concerning Job Creation - Dianita Prihandini (Authentica, 2022)
This research examines the change in status of an individual company to a limited liability company based on Article 153H of the Government Regulation in Lieu of Law of the Republic of Indonesia Number 2 of 2022 concerning Job Creation. The problems formulated are, first, how the role of the Notary in the process of changing the status of the individual company and second how the legal consequences arising from the change in the status of the individual company based on the Government Regulation in Lieu of the Law of the Republic of Indonesia on Job Creation. This type of research is normative juridical with a statutory approach and conceptual approach. The method used is a literature study, and the data is processed non-statistically and assessed descriptively and qualitatively. The results of the study concluded, first, that there is a role of a Notary in the change of status, namely, first as an official authorized to make deeds in the process of changing status, second, registering changes in the status of individual companies to the Minister of Law and Human Rights of the Republic of Indonesia, as regulated in the government regulation in lieu of the law and its implementing regulations, namely the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 21 of 2021 concerning Requirements and Procedures for Registration, Establishment, Changes, and Dissolution of Limited Liability Companies, secondly, the legal consequences for individual companies that change their status, namely that the individual company is not dissolved first, but continues to be a limited liability company with the capital partnership. Keywords: the role of Notary; Individual Company; status change.